Neuroendocrine Tumour Arising from a Colonic Mesenteric Cyst - Razrim Rahim; M. Sharifuddin Abu Bakar; Diana Melissa Dualim; Rashidah Mohd Khalid (Surgical Society of Northern Greece, 2024)
Indexed by Scopus